Emotional Intelligence and Burnout among Adolescent Basketball Players: The Mediating Effect of Emotional Labor - Wenjun Xue; Yiming Tao; Yangyi Huang; Guannan Liu; Huiru Wang (Sports, 2024)
Burnout, characterized by emotional and physical exhaustion, poses a significant challenge to adolescent athletes, particularly in high-intensity sports like basketball. Emotional Intelligence (EI) is the ability to manage emotions, which is negatively associated with burnout. Emotional labor, including strategies of surface acting (SA), deep acting (DA), and genuine expression (GE), plays a potentially key role in emotion management between EI and burnout for athletes. This study aims to investigate the relationship between EI and burnout, as well as the mediating role of emotional labor strategies among adolescent basketball players. Our cross-sectional study, conducted in youth sports schools in four different places in China, involved 260 basketball players. Results indicate a negative association between EI and burnout, with SA and GE emerging as significant mediators. SA was positively linked to burnout, while GE showed a negative association. These findings suggest that enhancing EI and managing emotional labor strategies are crucial for mitigating burnout and improving the well-being and performance of young athletes.